CLIMATIC WATER BALANCE AND CLIMATIC CLASSIFICATION FOR PARANAVAÍ MUNICIPATILITY, PARANÁ - Lopes, Allan Remor; Dotto, Marcelo; Xavier, Elouize; Giarola, Camila Moreno; Pirola, Kelli (Revista Brasileira de Engenharia de Biossistemas, 2021)
Understanding the climatic conditions of the Paranavaí municipality must be considered due to its importance in the national agriculture scenario. In this study, we calculated the climatological water balance (CWB) by performing the climate classification using the method of Thornthwaite and Mather for the municipality of Paranavaí, Paraná. We used temporal series from 1975 to 2018, and we adopted a 100 mm value for the available water capacity (AWC). Paranavaí presented an annual precipitation average of 1523,8 mm, and 1090,62 mm of evapotranspiration. The municipality presented only one month with a water deficit (August) and eleven months with a water surplus (September to July). Regarding climate classification, was found C1dA’a’s climate, characterized as a mesothermal climate with little or no water déficit.